Frequência alélica da variante dmrt3 g.22999655c>a (equcab2.0) em asininos e muares com marcha batida ou picada - Herman, Mariana [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The DMRT3:g.22999655C>A SNP influences the gait types of horses, and the wild-C and mutant-A alleles have been associated with batida and picada gaits, respectively. Donkeys and mules also have batida or picada gaits, and this study aimed to determine the allele frequency of the DMRT3 SNP in gaited donkeys and mules and to verify whether the genotype influences the type of gait in these animals. Thus, 159-mules and 203-donkeys were genotyped. Among the 159 mules assessed, 47% had a CC genotype, and 53% had a CA genotype. The CC genotype was predominant in the donkeys (97%). The AA genotype was not found in the mules or donkeys. The CC and CA genotypes were similarly distributed in the mule group with batida or picada gaits. The frequencies of the CC genotype in the donkeys were similar, regardless of whether the gait was batida or picada. However, the CA genotype was more frequent in donkeys with a picada gait than in those with a batida gait. The previous description of the three genotypes in Mangalarga and Campolina horses, which are the main breeds involved in the production of marching mules in Brazil, explains the higher percentage of CA mules and the very low presence of the mutated allele in donkeys, allowing us to speculate that the mutated allele was inherited from the mares used in the crosses with donkeys. In addition, these results suggest that the gait is not influenced by the aforementioned mutation and that other genes and polymorphisms may influence the trait in equids.

A variação do gene DMRT3_chr23:g.22999655C>A está correlacionada com tipo de marcha nos equinos, o alelo selvagem-C e o mutante-A foram associados com a marcha batida e picada respectivamente. Jumentos e muares também apresentam marcha batida e picada, e esse estudo objetivou a determinação da frequência do alelo DMRT3 SNP em jumentos e muares marchadores, além de determinar se o genótipo influenciaria diretamente o andamento nesses animais. Para tanto, foram genotipados 159 muares e 203 jumentos. Dentro da amostragem de muares 47% tinham genótipo CC e 53%CA. Já o genótipo CC foi predominante nos jumentos (97%). O genótipo AA não foi encontrado nos muares nem nos jumentos. Ambos os genótipos estavam distribuídos de maneira similar nos muares com o andamento marchado batido ou picado. Já o genótipo CC estava presente na maioria da amostragem independente do andamento, fosse ele picado ou batido, entre os asininos. Já o genótipo CA em asininos mostrou-se mais frequente em jumentos de andamento picado do que naqueles de marcha batida. Os relatos existentes desses três genótipos nas raças Mangalarga e Campolina, as duas principais raças usadas na produção de muares no Brasil, explicam a maior incidência do genótipo CA nos muares e a baixíssima incidência do alelo mutado nos asininos. Nos permitindo especular que o alelo mutado frequente nos muares foi herdado das éguas usadas nos cruzamentos com os jumentos. Finalmente, esses resultados sugerem que a marcha em questão não é influenciada pela mencionada variante e que demais genes e polimorfismos podem justificar essa característica em equídeos.
Allele frequency of DMRT3 g.22999655C>A (EquCab2.0) variant in donkeys and mules with batida or picada gaits
Keywords: Equídeos; PCR-RFPL; Marcha; Genotipagem; Equids; Gait; Genotyping; Brasil; Brazil